TCT RUSSIA - XVI MOSCOW INTERNATIONAL COURSE ON ROENTGEN-ENDOVASCULAR DIAGNOSTICS AND THERAPY HAS FINISHED ITS WORK (Столичная издательская компания, 2015)
TCT Russia - XVI Moscow international course on roentgen-endovascular diagnostics and therapy has finished its work.